Plasmonics of Au/Polymer Core/Shell Nanocomposites for Thermoresponsive Hybrid Metasurfaces - Magnozzi, Michele; Brasse, Yannic; Koenig, Tobias A. F.; Bisio, Francesco; Bittrich, Eva; Fery, Andreas; Canepa, Maurizio (ACS Applied Nano Materials, 2020)
We investigated the temperature-dependent optical response of ordered lattices of noninteracting gold-core/poly(N-isopropylacrylamide)-shell nanoparticles (NPs), a system with proven photothermal and sensing capabilities. For the first time on this system, we exploited in situ spectroscopic ellipsometry (SE) to determine the complex, temperature-dependent optical properties of the lattice - a key piece of information which, however, is often overlooked. In doing so, we took full advantage of large-scale colloidal self-assembly, which makes NP lattices accessible to conventional SE. A quantitative interpretation of the SE data was obtained through an effective model based on the actual characteristics of the NPs and their dielectric environment. The model allowed to estimate temperature-dependent morphological parameters, such as the distance between the gold cores and the substrate, also yielding the complex permittivity of the plasmonic NP lattice. Thus, by combining the high sensitivity of SE with proper modeling, we provide a comprehensive characterization of thermoresponsive NP lattices. The approach proposed here is instrumental to the analysis and design of functional hybrid metasurfaces with plasmonic functionalities, including particle-to-film coupled systems.
CRIS-Team Scopus Importer:2022-04-14
Keywords: complex permittivity; core-shell particles; localized surface plasmon resonance; PNIPAM; spectroscopic ellipsometry